Colocalization of Bunina bodies and TDP‐43 inclusions in a case of sporadic amyotrophic lateral sclerosis with Lewy body‐like hyaline inclusions. Issue 5 (25th June 2018) - Miki, Yasuo; Mori, Fumiaki; Seino, Yusuke; Tanji, Kunikazu; Yoshizawa, Tadashi; Kijima, Hiroshi; Shoji, Mikio; Wakabayashi, Koichi
Abstract : Sporadic amyotrophic lateral sclerosis (sALS) is characterized pathologically by loss of upper and lower motor neurons with occurrence of transactivation response DNA‐binding protein 43 kDa (TDP‐43)‐immunoreactive skein‐like and round hyaline inclusions. Lewy body‐like hyaline inclusions (LBHIs) are also found in a small proportion of sALS cases as well as in individuals with familial ALS with mutations in the Cu/Zu superoxide dismutase (SOD1) gene. LBHIs in sALS are immunopositive for TDP‐43, but not for SOD1. The occurrence of Bunina bodies (BBs) is another key pathological feature of sALS. BBs are immunonegative for TDP‐43 but immunopositive for cystatin C, transferrin, peripherin and sortilin‐related receptor CNS expressed 2 (SorCS2). Despite differences between BBs and TDP‐43 inclusions in terms of protein constituents and ultrastructure, the two inclusions are known to be linked. We recently encountered a case of sALS of 10 months duration in which many round hyaline inclusions, LBHIs and BBs were found in the anterior horn cells of the spinal cord. Our immunohistochemical and ultrastructural examinations revealed the presence of BBs within the skein‐like and round hyaline inclusions, and in the LBHIs. Colocalization of BB‐related proteins (cystatin C, transferrin and SorCS2) and TDP‐43 was also confirmed in the halo of LBHIs as well as in the marginal portion of the skein‐like and round hyaline inclusions. These findings suggest that there is some relationship between BBs and TDP‐43‐immunoreactive inclusions in terms of their formation processes.